ADVOKASI BUYA HUSEIN MUHAMMAD DALAM PENINGKATAN PARTISIPASI POLITIK PEREMPUAN - Baharudin Baharudin; Dayu Aqraminas (Harakat an-Nisa: Jurnal Studi Gender dan Anak, 2021)
This paper informs about the advocacy made by Buya Husein Muhammad in increasing women's participation in politics. The study used descriptive-analytical methods. Descriptive methods are used to describe and describe KH's thoughts. Husein Muhammad on a problem topic and in comparative analysis. The results showed that Buya Husein Muhammad's role to increase women's participation in politics was carried out through three procedural approaches, namely advocating for women's politics, namely cultural reconstruction, constitution, and religion.